2022-RA-1165-ESGO Feasibility and safety of inguinofemoral sentinel lymph node biopsy for previously excised vulvar cancer. (20th October 2022) - Pascoal, Erica; Alyafi, Mohammad; Pokoradi, Alida; Eiriksson, Lua; Helpman, Limor
Abstract : Introduction/Background: Performing inguinofemoral sentinel lymph node biopsy (IFSLNB) for vulvar cancer following a previous vulvar excision, often referred to as 'scar injection, ' is currently debated. Our study aimed to assess the feasibility and safety of IFSLNB following scar injection. Methodology: We conducted a retrospective observational study of patients with vulvar cancer, who underwent IFSLNB following radiotracer injection around a tumour or around a scar following previous vulvar excision. IFSLN detection rates are described per patient and per groin and are compared using chi-square analysis. We performed a Cox regression analysis to assess the association of recurrence and survival with vulvar injection site and recognized pathological variables. Results: Data was analyzed for 173 groins in 97 patients. At least one IFSLN was detected in 94% of groins examined, and IFSLN detection rate did not differ whether the groin was assessed following tumour injection (n=122, 94%) or scar injection (n=40, 93%; p =0.85). Patients in the scar injection group had less frequent IFLN metastases ( p =0.019), smaller tumours ( p< 0.001) and more superficial invasion ( p <0.02). Median overall follow-up from surgery to death or censoring was 34.7 (range 0–108) months. Cox regression analysis demonstrated that scar injection was not an independent predictor of recurrence or death, and depth of invasion was the only independent predictor of disease recurrence (HR 1.14, p =0.029). Conclusion: Our observations support the feasibility and safety of scar injection as an alternative to full lymphadenectomy and should be validated in a prospective study with a more robust sample size.